Arteriovenous fistulas in the craniocervical junction region: With vs. without spinal arterial feeders - Song, Zihao; Ma, Yongjie; Wang, Yinqing; He, Chuan; Li, Guilin; Zhang, Peng; Hong, Tao; Sun, Liyong; Hu, Peng; Ye, Ming; Zhang, Hongqi (Frontiers in Surgery, 2023)
Objective: Arteriovenous fistulas (AVFs) in the craniocervical junction (CCJ) region are a rare occurrence with special clinical manifestations. This study retrospectively reviewed patients with CCJ AVFs treated at our neurosurgical center, aiming to enhance the understanding of CCJ AVF. Methods: A total of 113 patients with CCJ AVFs treated at our neurosurgical center between January 2013 and December 2020 were enrolled. They were grouped as patients with CCJ AVFs with spinal arterial feeders (n=20) and patients with CCJ AVF without spinal arterial feeders (n=93). Clinical presentation, angiographic characteristics, intraoperative findings, and treatment outcomes were analyzed. Results: The patients’ median age was 55 years (IQR 47.5-62 years). The proportion of male in the group without spinal arterial feeders was significantly higher(p=0.001). Subarachnoid hemorrhage (SAH) was the most common clinical presentation, especially in the group with spinal arterial feeders(p<0.001). There were significant differences in AVF type, fistula location and direction of the venous drainage between the two groups(p<0.001). Intervention embolization combined with microsurgery was more common in treating AVF with spinal arterial feeders (p=0.006). Spinal arterial feeders did not appear to affect the outcome (p=0.275). Conclusions: SAH was the most common presentation of CCJ AVFs in this study. Microsurgery and interventional embolization were optional treatment strategies. The angioarchitecture of CCJ AVF was essential for selecting treatment strategies.